2023
DOI: 10.1080/21655979.2023.2255423
|View full text |Cite
|
Sign up to set email alerts
|

Screening ester-producing yeasts to fortify the brewing of rice-flavor Baijiu for enhanced aromas

Chunyun Qu,
Liying Peng,
Yongtao Fei
et al.

Abstract: To enhance the aromas in Guangdong rice-flavor Baijiu, ester-producing yeast was selected to fortify Baijiu brewing. Among eight kinds of ester-producing yeasts selected, Saccharomyces cerevisiae CM15 (CM15) that showed both the stronger ability to utilize substrates to produce esters and the excellent tolerance to industrially relevant stress factors was chosen. When CM15 was synergistically fermented with six kinds of Kojis from distilleries of rice-flavor liquor in Guangdong, the enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Biofortification of Baijiu microecology with functional strains can optimize the microbial community structure, flavor metabolism, and yield output of the fermentation system [ 71 , 86 ]. The effects of biofortification on Baijiu fermentation are many and varied.…”
Section: Microbiota Regulation Of Baijiu Based On Functional Strains ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Biofortification of Baijiu microecology with functional strains can optimize the microbial community structure, flavor metabolism, and yield output of the fermentation system [ 71 , 86 ]. The effects of biofortification on Baijiu fermentation are many and varied.…”
Section: Microbiota Regulation Of Baijiu Based On Functional Strains ...mentioning
confidence: 99%
“…In order to improve the yield and quality of Baijiu, high production of esters has been used as a requirement for the screening of target yeast strains. After obtaining the target strains, the researchers increased the content of esters such as ethyl hexanoate and ethyl acetate in Baijiu by making fortified Daqu or pure-strain suspensions [ 38 , 71 , 87 ]. It has also been shown that the addition of a single exogenous yeast strain also increases the levels of compounds such as ethanol, phenylethanol, and tetramethylpyrazine in the fermentation system [ 83 ].…”
Section: Microbiota Regulation Of Baijiu Based On Functional Strains ...mentioning
confidence: 99%